Evidence of destructive debris flows at (pre-) Hispanic Cayambe settlements, Ecuador. (10th October 2022) - Vasconez, Francisco J.; Samaniego, Pablo; Phillips, Jeremy; Andrade, S. Daniel; Simbaña, Edwin; Nogales, Valeria; Román-Carrión, José Luis; Vásconez Müller, Anais; Vásquez, María Antonieta
Abstract: In Ecuador, a country with numerous potentially active volcanoes, recurrent large earthquakes, and regular climate-related events, it is surmised that phenomena such as debris flows have affected pre-Hispanic populations since their settlement in ∼5000 cal BC. Here, using a multidisciplinary approach, we studied the most recent debris flow events that affected the Cayambe city area, located 15 km west of the active glacier-clad Cayambe volcano. Based on detailed characterization of the deposits, including sedimentological, archaeological, and paleontological analyses, as well as radiocarbon dating. We found that two debris flow (i.e., Río Blanco I and II) destroyed Caranqui settlements in 665–775 cal AD and 774–892 cal AD, respectively, while another event impacted a Spanish colonial farm in 1590–1620 cal AD (Río Blanco III). The grain size distribution of these deposits indicates a gravel-rich flow for Río Blanco I and clay-rich flow for Río Blanco II and III, whilst componentry suggests low juvenile volcanic content for all three deposits. Juvenile components include pumice and lustrous dense dacites, while accidental clasts are dull dense dacites, oxidized and hydrothermally-altered material, as well as archaeological artifacts. These results, in addition to radiocarbon ages, suggest that the debris flows could either be post-eruptive or not related to volcanic eruptions. Potential non-volcanic trigger mechanisms for these events include rainfall and/or earthquakes, which implies that they can occur at any time and without forecast. Currently, the city of Cayambe is rapidly expanding and, consequently, our findings are relevant for creating impact scenarios for future debris flows forming in the Rio Blanco headwaters and descending to the city.